Intravenous ondansetron induced hypersensitivity reaction: a case report - Nitya, S.; Shanthi, M.; Meenakshi, R.; Kiruthika, S. (International Journal of Basic & Clinical Pharmacology, 2021)
Ondansetron a selective 5-HT3 receptor antagonist has been widely used as a prophylactic antiemetic for chemotherapy induced and anaesthesia related nausea and vomiting. Anaphylaxis and anaphylactoid reaction rarely occur in less than 1% of the patients and may lead to potentially life-threatening events. This study is one such rare case report of hypersensitivity reaction to intravenous ondansetron in a perioperative setting. Familiarity about anaphylactoid reactions to intravenous ondansetron among the health practitioners would help them to bring about a rational approach to decrease its incidence.